Type 2 diabetes mellitus increases liver transplant-free mortality in patients with cirrhosis: A systematic review and meta-analysis - Liu, Zi-Jin; Yan, Yi-Jie; Weng, Honglei; Ding, Hui-Guo (World journal of clinical cases, 2021)
Type 2 diabetes mellitus increases liver transplant-free mortality in patients with cirrhosis: A systematic review and meta-analysis
Gesehen am 21.06.2022